Differentiation of malignant from benign orbital tumours using dual-energy CT. Issue 4 (April 2022) - Luo, S.; Sha, Y.; Wu, J.; Lin, N.; Pan, Y.; Zhang, F.; Huang, W.
Abstract : AIM: To investigate the diagnostic accuracy of dual-energy computed tomography (DECT)-derived iodine concentration (IC), effective atomic number (Zeff ), and spectral attenuation information for differentiating malignant and benign orbital tumours. MATERIALS AND METHODS: Data from 41 patients with orbital tumours from November 2019 to March 2021 were analysed retrospectively. Each patient underwent contrast-enhanced DECT using a 128-section dual-source computed tomography (DSCT) system. Dual-energy information, including IC, normalised iodine concentration (NIC), Zeff, virtual monoenergetic images (VMIs) reconstructed from 40 to 120 keV and slope (k) value were determined. Quantitative measurement of DECT parameters was undertaken by two independent radiologists blinded to clinical data. Differences in parameters were assessed using independent sample t -test. Diagnosis performance was calculated by the receiver operating characteristic (ROC) curve analysis. Radiation doses of conventional CT and DECT were compared by paired t -tests. RESULTS: Forty-one patients with histopathologically confirmed tumours were enrolled, including 10 malignant cases and 21 benign cases. Malignant orbital tumours exhibited significantly greater IC, NIC, Zeff, CT attenuation of VMIs at 40–105 keV, and k values compared to benign orbital tumours ( p< 0.05). In ROC analyses, 40 keV VMI demonstrated the highest diagnostic performance of single parameters (area under the ROC curve [AUC], 0.940), and combined parameters achieved the best performance (AUC, 0.971; sensitivity, 90%; specificity, 93.55%). Radiation doses were significantly reduced in DECT than conventional CT ( p< 0.001). CONCLUSIONS: Quantitative DECT analysis can be a useful technique, which yields excellent diagnostic accuracy, in the differentiation of malignant and benign orbital tumours with low radiation dose. Highlights: DECT parameters enable to distinguish malignant from benign orbital tumors. The combination of multi-parameters can increase the predictive efficiency. Considerable radiation dose reduction is obtained using DECT technology.